Assured cloud computing - Campbell, Roy Harold; Kamhoua, Charles A.; Kwiat, Kevin A. (IEEE Computer Society, Inc./Wiley, 2018)
Explores themes that drive individual contributions, including design correctness, support for big data and analytics, monitoring and detection, network considerations, and performance - Synthesizes highly cited earlier work (on topics including DARE, trust mechanisms, and elastic graphs) as well as newer research findings on topics including R-Storm, and RAMP transactions - Addresses assured cloud computing concerns such as game theory, stream processing, storage, algorithms, workflow, scheduling, access control, formal analysis of safety, and streaming Marketing Description: IEEE Computer Society, the IEEE Reliability Society, and the IEEE Systems, Man, and Cybernetics Society--